The dual pathways of influence in live commerce: How brand engagement moderate online social interactions, sharing experience and impulsive purchases across Thai and Chinese consumers - Rattanapun, Supot; Pringle, Nisaphan; Prompes, Pornprom; Khantanapha, Kriengsak; Hao, Richard (Edelweiss Applied Science and Technology, 2025)
Psychological factors drive impulsive buying in live commerce across consumer marketplaces. This study examines how online emotional and informational interactions affect consumer behavior in live commerce platforms. The main objectives are to (1) examine the effects of online emotional interaction (OEI) and online information interaction (OII) on experience sharing (SE); (2) to examine how experience sharing affects consumers’ impulsive purchasing behavior (CIP); (3) to assess brand engagement’s moderating role on the relationship between online interaction and experience sharing; and (4) to compare these relationships between Thai and Chinese consumers. Structured questions were given to 205 Thai and Chinese live streamers. The questionnaire data was examined using SEM and multigroup analysis. The study found that: (1) online emotional interaction (OEI) significantly affects impulsive purchases (β = 0.28); (2) OII has a significant effect (β = 0.18); (3) experience sharing (SE) strongly predicts impulsive buying behavior (β = 0.41), emphasizing social validation and peer influence; and (4) brand engagement (BE) significantly enhances impulsive purchases (β = 0. Multi-group analysis showed a significant difference in brand engagement (BE) through impulsive purchase behavior (CIP) between Thai and Chinese consumers, with a higher effect for Chinese respondents (β = 0.40) compared to Thai respondents (β = 0.29, p = 0.04). These findings emphasize the importance of online social contact and brand involvement in creating impulsive live commerce purchases and cultural differences between consumer groups. The study helps explain how emotional, informational, and brand elements interact in digital retail.